Сучасні підходи до вивчення іноземної мови студентами ЗВО - Черничко Степан; Csernicskó István; Csernicsko Istvan; Берегсасі Аніко; Beregszászi Anikó; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina (Видавництво «Код», 2025)
Резюме. Сучасні методи підтвердили свою ефективність у роботі із викладанням англійської мови для майбутніх фахівців. У цьому контексті додаємо більш детальні рекомендації щодо їхнього використання на практиці. Важливими є засоби, які сприяють залученню сучасних методик викладання та їх реалізації (мобільні девайси). За допомогою смартфона навчання стає доступнішим. Є багато різних додатків та освітніх платформ, завдяки яким вчитися стало легше та веселіше. Для підвищення мотивації вивчення англійської мови в університеті, для стимулювання більш активної роботи студентів на парах, викладачеві слід постійно вдосконалювати методичні прийоми, які розкрито у статті.

Abstract. Modern methods have proven their effectiveness in teaching English to future professionals. In this context, we add more detailed recommendations on their use in practice. The article focuses attention and reveals the content of innovative modern methods of the educational process: the method of suggestopedia, which is based on the simultaneous application of the processes of conscious and unconscious perception; the method of situational language learning, which emphasizes educational counseling, in which the teacher plays the role of a language consultant; the method of full physical reaction aimed at reducing stress when learning a foreign language; communicative method – learning promotes language fluency; the CLIL method, which is based on teaching the subjects of the program in English; Blended learning is a mixed form of learning in which both face-to-face teaching and online learning are combined; Embodied learning is another relevant method in which learning is a physical process, not just a mental one; Inquiry based learning promotes student-centered learning; the webquest method, which is defined as a student’s research activity. Means that contribute to the involvement of modern teaching methods and their implementation (mobile devices) are important. With the help of a smartphone, learning becomes more accessible. There are many different apps and educational platforms that make learning easier and more fun. You can use the programs Quizlet, ELSA (helps with correct pronunciation), Busuu (allows you to remember words in the context of various dialogues, and those who have a paid account can complete the task and send it to a native speaker test). In order to increase the motivation to study English at the university, to stimulate more active work of students in pairs, the teacher should constantly improve the methodical techniques disclosed in the article.
Modern approaches to learning a foreign language by high school students
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: сучасні підходи до освітнього процесу; заклади вищої освіти; іноземна мова; студенти; інноваційні методи освітнього процесу